TELAAH NILAI-NILAI MODERASI BERAGAMA DALAM SERIAL ANIMASI UPIN-IPIN MUSIM SEPULUH - A, Tania Nafida; Bayu H, Putri; Dzulfahmi, Adib (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
Religious moderation is an effort to deal with differences in religion. Religious moderation can be interpreted as a moderate attitude towards differences and diversity. Moderari religion means trying to take a middle or neutral position between two views or differences and is an attitude that seeks to listen to each other and can live in a society full of diversity properly. In this study, we will analyze the value of moderation in the animated series Upin-Ipin and relate it to the religious moderation manual issued by the Indonesian Ministry of Religion. This study aims to determine whether the value of moderation displayed in the animated series Upin-Ipin season ten